Dynamic simulation models for seismic behavior of soil systems - Part I: Block diagrams - Sahin, Abdurrahman (TECHNO-PRESS, 2015)
Digital simulation has recently become the preferred method for designing complex and dynamic systems. Simulation packages provide interactive, block-diagram environment for modeling and simulating dynamic models. The block diagrams in simulation models are flowcharts which describe the components of dynamic systems and their interaction. This paper is the first part of the study for determining the seismic behavior of soil systems. The aim of this part is to present the constructed block diagrams for discrete-time analysis of seismic site amplification in layered media for vertically propagating shear waves. Detailed block diagrams are constructed for single and multiple soil layers by considering wave propagation with and without damping, respectively. The block diagrams for recursive filter to model attenuation in discrete-time form are also constructed. Finite difference method is used for strain calculation. The block diagrams are developed by utilizing Simulink which is a software add-on to Matlab.
Keywords: seismic site amplification; soil dynamics; digital simulation; simulink; matlab; SITE RESPONSE ANALYSIS; GROUND MOTION; Engineering